2004
DOI: 10.3233/jad-2004-6509
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Aβ(1–42) exhibits oxidative stress properties similar to those of human Aβ(1–42): Implications for proposed mechanisms of toxicity

Abstract: Alzheimer's disease is a neurodegenerative disorder associated with aging and cognitive decline. Amyloid beta peptide (1-42) [Aβ(1-42)] is a primary constituent of senile plaques-a hallmark of Alzheimer's disease-and has been implicated in the pathogenesis of the disease. Previous studies have shown that methionine residue 35 of Aβ(1-42) may play a critical role in Aβ(1-42)-mediated oxidative stress and neurotoxicity. Several additional mechanisms of neurotoxicity have been proposed, including the role of Cu(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 51 publications
8
44
0
3
Order By: Relevance
“…At the same time, however, other studies have found evidence for a ROS detoxication role of A (100). Thus, despite the plethora of studies, more work will be needed if the field is going to reach a consensus on the role of A as being neurotoxic or neuroprotective (179), how either activity is modulated by metal complexation (180), and how dynamics of A aggregation alter neurotoxic vs neuroprotective properties as a function of time course of the disease. It must be appreciated that Amediated ROS generation could be unique to in vitro cellular systems, since there is no evidence that A causes oxidative stress in vivo (17).…”
Section: Role Of Oxidative Stress In Admentioning
confidence: 99%
“…At the same time, however, other studies have found evidence for a ROS detoxication role of A (100). Thus, despite the plethora of studies, more work will be needed if the field is going to reach a consensus on the role of A as being neurotoxic or neuroprotective (179), how either activity is modulated by metal complexation (180), and how dynamics of A aggregation alter neurotoxic vs neuroprotective properties as a function of time course of the disease. It must be appreciated that Amediated ROS generation could be unique to in vitro cellular systems, since there is no evidence that A causes oxidative stress in vivo (17).…”
Section: Role Of Oxidative Stress In Admentioning
confidence: 99%
“…[44][45][46][47] Moreover, in the cascade of pathological events in AD, and possibly in ageing, the oxidative stress could be an important factor in the stimulation of the amyloidogenic pathway of the APP (amyloid precursor protein) and in the formation/accumulation of b-amyloid peptides. [48][49][50][51] If this theory is correct, other neurotoxicants increasing the formation of free radicals …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the sequence of the amyloid varieties in many mammals, such in rodents, contains aminoacid substitutions compared to the human sequence and are less likely to form larger b-structures although they produces a similar oxidative stress. 50 It should be noted that demonstration of amyloid peptides in brain of young animals has not been published up to day. Moreover, very different results have been observed using distinct antibodies against different amino acid sequences of amyloid peptides in aged animals when amyloid deposits have been studied.…”
Section: Effects On Brain Protein Structure and Oxidative Stress 443mentioning
confidence: 99%
“…With remarkably few exceptions (lab rodents), the Aβ sequence is identical in other vertebrates, including zebra fish (Coulson et al 2000). The absence of diffuse Aβ plaques in old lab rodents may be attributed to three amino acid differences that slow aggregation (Boyd-Kimball et al 2004). Besides its role in neurotoxicity (Klein et al 2001;Hardy 2009), the Aβ peptide also has strong anti-microbial activity (Soscia et al 2010), suggesting a basis for its evolutionary stability.…”
Section: Species Differences In Relevant Genesmentioning
confidence: 99%
“…Whereas all primates examined share the same β-amyloid (Aβ1-42) amino acid sequence with humans, the Aβ peptide of lab rodents diverges from primates in three amino acids that reduce its spontaneous aggregation (Boyd-Kimball et al 2004). The absence of brain Aβ deposits in aging rodents gives an important comparative control in aging mechanisms because Aβ is pro-inflammatory and can activate astrocytes and microglia.…”
Section: Primate Neurobiologymentioning
confidence: 99%